Effect of the Anode Placement on the Antagonist Muscles Recruitment: Implication for the Interpolated Twitch Technique Outcome. - Piponnier, Enzo; Thorkani, Ashref; Zghal, Firas; Cottin, François; Martin, Vincent (Journal of Sports Science & Medicine, 2019)
The aim of the present study was to compare the recruitment of the antagonist muscles and its effect on the measurement of the voluntary activation level (VA) of the knee extensor (KE) muscles for different anode placements used to stimulate the femoral nerve. We hypothesized that when the anode is positioned over the gluteal fold (GF), the antagonist muscles recruitment would be greater and, thus the VA overestimated, than when the anode is placed midway between the greater trochanter and the lower border of the iliac crest (Midtroc-iliac). Thirteen healthy men (23 ± 4 yr) were tested in both conditions (GF vs. Midtroc-iliac) in a randomized order. Recruitment curves were performed to determine the optimal stimulus intensity (Iopt) and quantify antagonist muscles recruitment (i.e. biceps femoris M-wave). Participants performed maximal voluntary isometric contractions (MVIC) and the interpolated twitch technique was used to measured VA. Antagonist muscles recruitment was greater when the anode was placed over the GF than Midtroc-iliac. The Iopt was also lower for GF than Midtroc-iliac placement. However, no significant effect of anode placement was found for the interpolated twitch technique outcome. When the anode was placed over the GF, antagonist muscles recruitment was greater, inducing optimal stimulus intensity underestimation. However, it did not affect VA assessment. To fully avoid this potential limitation, Midtroc-iliac anode placement should nevertheless be preferred for the KE neuromuscular function assessment, owing to the reduced recruitment of the antagonist muscles.